Identification of Morphological Characters of Cassava (Manihot esculenta Crantz) Local Varieties in Leihitu District, Central Maluku Regency - Frederikus S Sikteubun; Jacob R Patty; Francina Polnaya (JURNAL BUDIDAYA PERTANIAN, 2022)
Cassava (Manihot esculenta Crantz) which belongs to the Euphorbiaceae family is a plant that has long been known and cultivated by the people of Indonesia. The process of plant adaptation will cause changes in the shape, size, color and yield of plants. The Cassava breeding program in Indonesia aims to assemble varieties with a high yield, tolerance to major pests and diseases, non-intensive branching, good tuber shape, tolerance to certain soil and climatic conditions, and early maturity. This study aimed to obtain the morphological characters of several varieties of cassava in the Leihitu District. This research was conducted in Leihitu District, Central Maluku Regency, eight villages were used as research locations, namely Morella Village, Mamala Village, Hitu Messeng Village, Hitu Lama Village, Wakal Village, Hila Village, Kaitetu Village and Seith Village. This study used a descriptive analysis method. The results showed in 8 villages in Leihitu District, we found 8 different varieties of cassava plants, namely Inggris, Bistein, Keras/Pahit, Bubur/Lunak, Sukabumi, Kapok and Mentega. The diversity of cassava varieties was very high in Kaitetu Village, whereas the diversity was low in Morella Village and Mamala Village. Based on the dendrogram formed, there were 2 clusters, 3 clusters, 4 clusters, 5 clusters, 6 clusters, and 7 kinship clusters with a kinship distance scale of 5, 10, 11, 13, 18, and 25.